ANALISIS EFISIENSI PADI GOGO DI KECAMATAN WOLASI KABUPATEN KONAWE SELATAN - Nurmaya, Nurmaya; Harianti, Harianti; Hasriati, Hasriati; Rosmalah, Sitti (Agros Journal of Agriculture Science, 2024)
The production of lowland rice and swidden rice nationally continues to increase, but productivity is not constant. Based on data from BPS (2022), overall rice production and harvested area in Southeast Sulawesi province experienced a decline in growth in 2021 of around 127.52 ha compared to 2022 of around 118.26 ha. For productivity there was negative growth. This condition is caused by several problems faced in these two types of rice farming. Lowland rice farming is facing the problem of decreasing rice field land caused by land conversion into residential and industrial land. The practice of cultivating upland rice in South Konawe Regency is carried out simply and traditionally, especially in the Wolasi District area. The cultivation pattern applied is organic-based farming. This system is very good to maintain because the products produced are free from chemicals and impacts on the environment can be avoided. However, judging from the productivity achieved, it is still very low. This phenomenon needs to be known and studied more deeply, especially the technical aspects of cultivating upland rice farmers. Based on the phenomena faced by researchers, this research aims to analyze the technical efficiency of upland rice farming in Wolasi District, South Konawe Regency. Technical efficiency is calculated using the DEA (Data Envelopment Analysis) program. The average efficiency of upland rice farming in Wolasi District reaches 65%. A total of 27 respondents 71.05%) were in the efficient category with an average efficiency value of 65%. However, productivity is still low due to the efficient scale achieved at the IRS stage, where the use of production factors can still be increased. Meanwhile, 11 respondents (28.95%) were technically inefficient Keywords: Efficiency, Upland Rice, Farming IntisariProduksi padi sawah maupun padi ladang secara nasional mengalami perkembangan yang terus meningkat, namun produktivitas tidak konstan.  Berdasarkan data dari BPS (2022) secara keseluruhan produksi padi dan luas panen provinsi Sulawesi Tenggara mengalami penurunan pertumbuhan pada tahun 2021 sekitar 127,52 ha dibandingkan tahun 2022 sekitar 118,26 ha.   Untuk produktivitas terjadi pertumbuhan negatif.  Kondisi ini disebabkan oleh beberapa masalah yang dihadapi pada kedua jenis usahatani padi ini.  Pada  usahatani padi sawah menghadapi masalah berkurangnya lahan persawahan yang disebabkan oleh alih fungsi lahan menjadi lahan pemukiman dan industri.   Praktik budidaya padi gogo di Kabupaten Konawe Selatan dilakukan secara sederhana dan tradisional, khususnya di daerah Kecamatan Wolasi.  Pola budidaya yang diterapkan yaitu pertanian berbasis organik. Sistem ini sangat baik untuk dipertahankan karena  produk yang dihasilkan bebas dari zat kimia dan dampak terhadap lingkungan dapat dihindari.  Namun dilihat dari produktivitas yang dicapai masih sangat rendah.  Fenomena ini perlu diketahui dan dikaji lebih dalam khususnya aspek teknis budidaya petani padi gogo.Berdasarkan fenomena yang dihadapi peneliti, maka penelitian ini bertujuan untuk menganalisis efisiensi teknis usahatani padi gogo di Kecamatan Wolasi Kabupaten Konawe Selatan.  Efisiensi teknis dihitung dengan menggunakan program DEA (Data Envelopment Analysis).  Rata-rata efisiensi usahatani padi gogo di Kecamatan Wolasi mencapai 65 %.  Sebanyak 27 responden 71,05 %) berada pada kategori efisien dengan nilai rata-rata efisiensi sebesar 65 %.  Namun segi produktivitas masih rendah karena skala efisien yang dicapai pada tahap IRS, dimana penggunaan faktor produksi masih dapat ditingkatkan.  Sedangkan sebanyak 11 responden (28,95 %) tidak efisien secara teknis Kata Kunci : Efisiensi, Padi Gogo, Usahatani